Exploring the market risk profiles of US and European stock insurers - Nicolaus Grochola; Mark J. Browne; Helmut Gründl; Sebastian Schlütter (Risk Management and Insurance Review, 2023)
Market risks account for an integral part of insurers' risk profiles. We explore market risk sensitivities of insurers in the United States and Europe. Based on panel regression models and daily market data from 2012 to 2018, we find that sensitivities are particularly driven by insurers' product portfolio. The influence of interest rate movements on stock returns is 60% larger for US than for European life insurers. For the former, interest rate risk is a dominant market risk with an effect that is five times larger than through corporate credit risk. For European life insurers, the sensitivity to interest rate changes is only 44% larger than toward credit default swap~of government bonds, underlining the relevance of sovereign credit risk.
Keywords: 330